Mappings : Feminism and the Cultural Geographies of Encounter - Friedman, Susan Stanford (Book collections on Project MUSE., 1998)
In this powerful work, Susan Friedman moves feminist theory out of paralyzing debates about us and them, white and other, first and third world, and victimizers and victims. Throughout, Friedman adapts current cultural theory from global and transnational studies, anthropology, and geography to challenge modes of thought that exaggerate the boundaries of gender, race, ethnicity, sexuality, class, and national origin. The author promotes a transnational and heterogeneous feminism, which, she maintains, can replace the proliferation of feminisms based on difference. She argues for a feminist geo.